Evaluation of Tomato Varieties for Higher Productivity in the NEH Region of India - Rangnamei, K. Lily; Kumar, Manoj; Meena, K. L.; Rajkhowa, D. J. (Indian Journal of Hill Farming, 2018)
On- farm trail was conducted in Longleng district of Nagaland during 2013-14 and 2014-15 to compare the phonological development and production potential of four varieties of tomato viz. MT-2, MT-3, Arka Meghali and Pusa Ruby (Local check) at farmers field under Krishi Vigyan Kendra Longleng. Data collected were plant height, branch per plant, number of fruits per plant, average fruit weight, fruit length, fruit breath and fruit yield. The experiment was laid out in Complete Randomized Block Design. The mean data of all the observation over two years were pooled and statistically analysed. The result revealed that maximum number of fruit/plant (43.44), fruit width were found under MT-2 whereas, plant height, average fruit weight recorded under Arka Meghali. Fruit weight of Arka Meghali and MT-2 were found statistically at par with each other. Maximum fruit yield (176.2 q/ha) and production efficiency (149.32 kg/ha/day) were recorded in MT-2 followed by Arka Meghali (173.1 q/ha, 132.14 q/ha) as compared to other tomato varieties. Gross income (Rs. 352400.00 per ha), net profit (Rs.251760.00 per ha), B:C ratio (3.49) and economic efficiency (2133.56 Rs/ha/day) were recorded highest under MT-2 as compared to other varieties.